Same Locus for Non-shattering Seed Pod in Two Independently Domesticated Legumes, Vigna angularis and Vigna unguiculata - Takahashi, Yu; Kongjaimun, Alisa; Muto, Chiaki; Kobayashi, Yuki; Kumagai, Masahiko; Sakai, Hiroaki; Satou, Kazuhito; Teruya, Kuniko; Shiroma, Akino; Shimoji, Makiko; Hirano, Takashi; Isemura, Takehisa; et al. (Frontiers in Genetics, 2020)
Loss of pod shattering is one of the most important domestication-related traits in legume crops. The non-shattering phenotypes have been achieved either by disturbed formation of abscission layer between the valves, or by loss of helical tension in sclerenchyma of endocarp, that split open the pods to disperse the seeds. During domestication, azuki bean (Vigna angularis) and yard-long bean (Vigna unguiculata cv-gr. Sesquipedalis) have reduced or lost the sclerenchyma and thus the shattering behavior of seed pods. Here we performed fine-mapping with back-crossed populations and narrowed the candidate genomic region down to 4 kbp in azuki bean and 13 kbp in yard-long bean. Among genes located in these regions, we found MYB26 genes encoded truncated proteins in azuki bean, yard-long bean and even cowpea. As such, our findings indicate that independent domestication on the two legumes have selected the same locus for the same traits. We also argue that MYB26 could be a target gene for improving shattering-phenotype in other legumes, such as soybean.